2017
DOI: 10.3892/mmr.2017.6807
|View full text |Cite
|
Sign up to set email alerts
|

Paecilomyces tenuipes extract prevents depression-like behaviors in chronic unpredictable mild stress-induced rat model via modulation of neurotransmitters

Abstract: The medicinal fungus Paecilomyces tenuipes exhibits a variety of pharmacological effects, including antidepressive effects. The chronic unpredictable mild stress (CUMS)‑induced rat model has served an important role in studies involving antidepressants screening. The aim of the present study was to evaluate the antidepressant‑like activity of P. tenuipes N45 aqueous extract (PTNE) in a CUMS‑induced rat model of behavioral despair depression. Following 4 weeks of PTNE treatment, behavioral tests were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Mice were randomly divided into nine groups (n = 10): Group CTRL (normal mice treated with physiological saline alone), Group DM (depression-like mice treated with physiological saline alone), Group Flu (depressionlike mice administrated 2.5 mg/kg fluoxetine hydrochloride orally for 15 days), Group AE (depression-like mice administrated orally 2500, 250 and 50 mg/kg of alcohol extract daily), Group WE (depression-like mice administrated orally 2000, 200 and 40 mg/kg of water extract) following the protocol [13]. All mice received 21 days of administration (once a day).…”
Section: Chronic Unpredictable Mild Stress-(cums) Induced Depression-mentioning
confidence: 99%
“…Mice were randomly divided into nine groups (n = 10): Group CTRL (normal mice treated with physiological saline alone), Group DM (depression-like mice treated with physiological saline alone), Group Flu (depressionlike mice administrated 2.5 mg/kg fluoxetine hydrochloride orally for 15 days), Group AE (depression-like mice administrated orally 2500, 250 and 50 mg/kg of alcohol extract daily), Group WE (depression-like mice administrated orally 2000, 200 and 40 mg/kg of water extract) following the protocol [13]. All mice received 21 days of administration (once a day).…”
Section: Chronic Unpredictable Mild Stress-(cums) Induced Depression-mentioning
confidence: 99%
“…At the end of each experiment, mice were removed from the water, dried using towels, and returned to normal temperature in warm air. The total immobility time of mice in the water was analyzed by video recording [14].…”
Section: Forced-swim Testmentioning
confidence: 99%
“…These results show that glycogen synthase kinase-3β may promote the progression of depression. Therefore, targeting glycogen synthase kinase-3β may be an effective therapeutic strategy.The chronic stress mouse model was produced via severe metamorphic stress [14,15]. The detailed procedure is illustrated in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, phytotherapy has become an attractive strategy in the treatment of many diseases . Previous studies found that many bioactive ingredients in Traditional Chinese Medicine (TCM) could alleviate insulin resistance through various mechanisms.…”
Section: Introductionmentioning
confidence: 99%